(untitled) (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2020)
The present work seeks to analyze, through the deductive and comparative approach method, using bibliographic research, the existing link between the concept of citizenship developed by Thomas Humprey Marshall, especially in the idea of ​​minimum economic well-being, with the social security law . Throughout the development of the work, it was noted that the social security law is contained in the so-called minimum economic well-being necessary for the development of citizenship, while it grants the citizen a minimum floor of financial conditions for the full exercise of their citizenship, that is, without this minimum guaranteed by social security, the very exercise of rights linked to citizenship would be compromised, while it would not bring the necessary freedom for the development of citizen freedoms.